2010
DOI: 10.1007/s12571-010-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

Bt crops and food security in developing countries: realised benefits, sustainable use and lowering barriers to adoption

Abstract: Transgenic crops producing insecticidal proteins from the bacterium Bacillus thuringiensis (Bt crops) have been cultivated commercially for over 15 years. Worldwide, Bt crops have provided effective control of target pests with fewer applications of insecticide, have increased yield and profitability for farmers, and have reduced risk to the environment and human health compared with non-Bt crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 98 publications
0
25
0
1
Order By: Relevance
“…Thus, the results in those laboratory tests are more conservative than studies conducted under Þeld conditions, and may better support the risk assessment because they provide robust data about the lack of toxicity of a test compound to a NTO (Duan et al 2010;Raybould 2007;Romeis et al, 2010). In addition, Tier-1 laboratory testing also allows general conclusions about the susceptibility of the test species to the toxins independent of the test crop varieties, thus the data can be expanded to other GE crops expressing the same toxin (Romeis et al 2006, Raybould andQuemada 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results in those laboratory tests are more conservative than studies conducted under Þeld conditions, and may better support the risk assessment because they provide robust data about the lack of toxicity of a test compound to a NTO (Duan et al 2010;Raybould 2007;Romeis et al, 2010). In addition, Tier-1 laboratory testing also allows general conclusions about the susceptibility of the test species to the toxins independent of the test crop varieties, thus the data can be expanded to other GE crops expressing the same toxin (Romeis et al 2006, Raybould andQuemada 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We also need to increase awareness of the environmental and health benefits of GE crops, which are rarely discussed in the media, such as reduced pesticide and fossil fuel usage in agriculture, reduced mycotoxin levels, and reduced exposure to toxic agrochemicals (Raybould and Quemada 2010;Sanahuja et al 2011). For example, the planting of Bt cotton has reduced pesticide applications by 50 % in India, avoiding up to 9 million poisoning incidents and saving $51 million (Kouser and Qiam 2011).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Cry1Ab and similar proteins, have been used extensively in transgenic crops worldwide, providing benefits to farmers, consumers and the environment in developed and developing countries. 14,28,86 The environmental and health risks from crops producing Cry1Ab are well characterized and negligible 18,62 and the data from which those conclusions are drawn are, in general, applicable to Bt cowpea; therefore, a preliminary assessment of Bt cowpea is that it too poses negligible risk.…”
Section: Summary-potential For Target Pest Populations To Evolve Resimentioning
confidence: 99%
“…The panel concluded that wild cowpea currently has low literature, stakeholders, the developers of the technology and, importantly, expert opinion. 19 Although protection goals are based on the social, cultural, economic and environmental objectives of a particular country, 28 there are some general environmental attributes, such as biodiversity and agricultural sustainability, that are routinely assessed worldwide for risks posed by insectresistant GM crops. The means by which these crops could harm these attributes include: (i) gene flow to wild relatives, (ii) the potential effects on non-target organisms (NTOs) (primarily arthropods) and (iii) insect resistance management (IRM).…”
mentioning
confidence: 99%